Promiscuous activity of ornithine decarboxylase from Enterobacter hormaechei: An alternative pathway for histamine formation in fermented sausages - Wei He; Binbin Li; Kaidi Hu; Xumei Zhong; Yulin Zhang; Jiamei Yu; Jiaxin Xie; Chengtao Li; Fengqin Li; Lanlan Wu; Shuhong Li; Jianlong Li; et al. (Food Microbiology, 2027)

Exercise and CD8+ T cells: mechanisms of immune modulation in antitumor responses - Li Liu; Zhihao Deng; Ruiying Fang; Mi Zou; Junlin Ren; Yuan Gao; Jie Peng; Liang Hao (Journal of Molecular Medicine, 2026)

Reconstruction of satellite remote sensing AOD considering spatial gap filling and downscaling - Xu Chen; Bowen Meng; Yun Peng; Huiyi Xiao; Bin Zou; Shoutao Zhu; Ning Liu; Shenxin Li; Xin Fang (Atmospheric Environment, 2026)

Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

Mechanistic insights into midgut injury in Bombyx mori induced by low concentration exposure to Bacillus thuringiensis - Hongbin Zou; Chaoli Fang; Guimin Nong; Xueling Qin; Bing Li (Pesticide Biochemistry and Physiology, 2026)

Enantioselective toxicity of pyriproxyfen to Apis mellifera and Sclerodermus guani and its impact on key genes in the juvenile hormone pathway - Lixia Zou; Wenjing Cao; Yan Fang; Jialin Liang; Yongheng Zhang; Suosheng Huang; Honghong Li; Xuesheng Li (Journal of Hazardous Materials, 2026)

Effects of host plants on the insecticide susceptibility of Spodoptera frugiperda - Yue Yuan; Yaqin Zou; Kaiyi Zeng; Wenyan Duan; Feiyue Ren; Liutong Ye; Jingjing Fang; Zhihong Xu; Xiaolei Zhang; Junkai Li (Journal of Pest Science, 2026)

Numerical investigation of star maneuvers of a self-propelled ship in pack ice conditions - Borui Yang; Biye Yang; Fang Li; Ming Zou; Guiyong Zhang; Aobo Zhang; Zhe Sun (Ocean Engineering, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Valorization of lithium slag into non-sintered lightweight aggregates: Long-term immobilization of Be/Tl and environmental safety evaluation - Zhang Zhihan; Zou Jiezhong; Cheng Shuping; Fang Chao; Rao Zhipeng; Wang Dong; Zeng Yanxi; Shi Qi; Qi Tao; Li Guobiao (Journal of Hazardous Materials, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Exogenous sodium nitroprusside alleviates cadmium toxicity in Solanum nigrum via antioxidant activation, metal redistribution, and gene expression modulation - Fang Yang; Jie Zou; Jinqun Feng; Ting Yu; Shuai Zhang; Shunqin Zhu; Wanhong Liu; Rui Li (Protoplasma, 2026)

The relationship between mutations in reverse transcriptase region of hepatitis B virus and progression of liver disease - Fang Jin; Dongli Li; Weihua Zou; Jianfeng Zhong; Zhaowei Tong; Fuchu Qian (Virus Genes, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

Rational design of Ag single-atom anchored ZnO nanoflower composites for synergistic antibacterial-ethylene scavenging in active fruit preservation - Yaqin Zhang; Runyu He; Yuqiao Fang; Yiming Li; Kaibin Gu; Sirui Liu; Zhiqun Zou; Yan Lv; Wenli Gao; Xingbo Shi (Chemical Engineering Journal, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Integrating magnetic nanoparticle-mediated isolation and synthetic microbial communities for efficient low-temperature straw degradation - Yi Fang; Jiaqi Li; Xuhong Ye; Li Zhang; Haozhe Lu; Youzhi Feng; Hongtao Zou (Journal of Environmental Chemical Engineering, 2026)

Calcium isotopes and thermodynamic calculations decipher fluorite mineralization in hydrothermal systems - Bin Xiao; Hao Zou; Di Yang; Ye Wan; Jianghan Wu; Jinxiang Shen; Franco Pirajno; Huidong Yu; Nuru Said; Huawen Cao; Fang Liu; Zhiwu Li; et al. (Geochimica et Cosmochimica Acta, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

Temperature-responsive microcapsule sachet enhances food preservation in cold chain through controlled ClO2 release and multimodal action - Runyu He; Fang Chen; Chunxuan Gao; Meng Li; Kaibin Gu; Zhiqun Zou; Jiahao Wu; Chunyi Luo; Xingbo Shi (Food Chemistry, 2026)

Rapid urine protein detection for CKD diagnostics using a high-sensitivity PDA-coated infrared fiber sensor - Shun Li; Ting Fang; Yongkun Zhao; Yinsheng Xu; Yami Ling; Ming Wang; Xiangpan Li; Jiang Zou; Wei Xiao; Guangchao Zang; Xianghua Zhang (Chemical Engineering Journal, 2026)

Lacto-N-triose II alleviates metabolic dysfunction-associated Steatotic liver disease via microbiota-dependent citrulline biosynthesis - Kaiwei Chen; Huiqing Yu; Bei Liu; Zizhen Yang; Wei Zhang; Yu Tian; Zhinan Wu; Haoyu Wang; Liang Xiao; Yiyi Zhong; Haifeng Zhang; Xu Fang; et al. (Food Research International, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Development of chitosan-based active composite films incorporating Chlorella vulgaris oil for active food packaging - Xiaotong Zou; Shaohua Zhao; Ke Liu; Lingtao Li; Miaosen Zhang; Rui Lu; Changqing Fang (Algal Research, 2026)

Earthworms Enhance Global Soil Carbon Storage Through Microbial–Mineral Stabilization - Yuanyuan Li; Jiahui Liao; Peter B. Reich; Yu Fang; Jiajie Cao; Juanping Ni; Tingting Ren; Guobing Wang; Xiaoming Zou; Honghua Ruan; Han Y. H. Chen (Global Change Biology, 2026)
Earthworms play a dual role in the global carbon cycle: they accelerate organic matter decomposition yet are often associated with greater soil organic carbon (SOC) storage. However, uncertainty regarding the mechanisms and magnitudes through which earthworms concurrently influence SOC mineralization and stabilization has limited the integration of soil fauna into carbon models. Here, we synthesize 696 paired observations from 122 studies worldwide to resolve this uncertainty. On average, earthworms increase SOC by 5.4% (95% CI: 2.2%–9.1%), with effects strengthening over time under sustained plant‐derived carbon inputs. Earthworms enhance mineral‐associated organic carbon (MAOC) by 21.2%, while particulate organic carbon (POC) remains unchanged. These patterns suggest that earthworm activity promotes a transition from short‐term carbon mineralization to long‐term stabilization, likely mediated by the coupling of microbial processing and physical protection. Specifically, epigeic earthworms boost microbial biomass carbon, whereas endogeic species enhance macroaggregate formation, facilitating the incorporation of microbial necromass into MAOC. The magnitude and direction of these effects depend on sustained carbon inputs and earthworm functional type. Collectively, these results reconcile decades of conflicting evidence and provide the first quantitative global synthesis showing that earthworms increased soil carbon over time under sustained plant carbon inputs. This microbial–mineral formation pathway has direct implications for climate‐smart land management, soil biodiversity conservation, and the representation of earthworm bioturbation in global carbon models.

Analysis of the antibacterial activity and mechanism of Litsea cubeba essential oil against Vibrio parahaemolyticus JD2305 causing translucent postlarvae disease - Qianhui Song; Laizhuang Jin; Di Fang; Na Ying; Lei Feng; Letian Li; Xiong Zou; Wenhong Fang (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Optimizing water and nitrogen management to balance yield and nitrogen loss in mechanically harvested low-stubble ratoon rice - Chaojie Lan; Hailong Xu; Bin Qin; Jinying Li; Bianhong Zhang; Jingnan Zou; Ting Chen; Jiahui Song; Zhihan Chen; Changxun Fang; Zhixing Zhang; Hongfei Chen; et al. (Field Crops Research, 2026)

Surface reconstruction steered nickel sulfides nanoarrays boost electrocatalytic upcycling of poly(ethylene terephthalate) plastic into formate coupled with H2 production - Ke'er Li; Zihan Liang; Muxin Fan; Qiongzhi Gao; Siyuan Yang; Shengsen Zhang; Yueping Fang; Dechun Zou; Xin Cai (Chemical Engineering Journal, 2026)

Group IIId ethylene responsive factor 34 as a positive modulator of ABA signal pathway in Arabidopsis - Li Zhang; Mingxin Piao; Luyao Ji; Zixun Gao; Pingping Wang; Zeng Zhou; Jinpeng Zou; Qingchi Shi; Fang Liu; Yuping Xie; Mingdi Bian; Zhenming Yang; et al. (Plant Science, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Incorporation of Schizochytrium limacinum oil-based pickering emulsion in chitosan active composite films for strawberry preservation - Xiaotong Zou; Shaohua Zhao; Kaiwei Xu; Ke Liu; Lingtao Li; Miaosen Zhang; Chang Yan; Xiaojuan Zhang; Changqing Fang (Food Research International, 2025)

Effects of geographical origin, processing and their interaction on stable isotopes in Pu-erh tea for traceability - Yanlong Li; Hai-Dan Zou; Xiao-Li Wang; Ming-Ming Chen; Bo-Wen Zhang; Wen-Fang Wang; Jie Li; He-Yuan Jiang; Li-Li Qian; Hong-Yan Liu (Food Chemistry, 2025)

Polymerizable deep eutectic solvent assisted facile preparation of lignin hydrogel with high transparency, adhesion and environmental tolerance for flexible electronics - Yutong Yang; Congcong Zhang; Yushan Zou; Zhenzhen Liu; Yiqun Fang; Weihong Wang; Min Xu; Yongming Song; Peng Li (Chemical Engineering Journal, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Comparative analysis of the WRKY gene family between Chimonanthus praecox and C. salicifolius - Wei Zou; Gui-Ting Hu; Fang-Fang Gui; Xin-Chen He; Priyanka Borah; Li Zhu; Hui-Juan Ning; Li-Yuan Yang (Genetica, 2025)

Vegetation dynamics in northwest China under climate Warming: Spatiotemporal heterogeneity and climate drivers - Shuangying Li; Yanyan Zhou; Dongxia Yue; Ying Zou; Fang Wang; Yulu Zan; Xuwei Sun (Journal of Environmental Management, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

New lignans from Phyllanthodendron dunnianum - Li Xu; Jian-Bing Tan; Yu-Ting Zheng; Zi-Huan Sang; Si-Yu Qin; Yuan-Tao Huang; Mei-Fang Li; Zhen-Xing Zou (Natural Product Research, 2025)

Influence of methylenetetrahydrofolate 677C > T variant in murine models following valproic acid exposure - Man Yang; Yinchao Li; Lei Lei; Shangnan Zou; Huanling Lai; Yue Xing; Yubao Fang; Qihang Zou; Yaqian Zhang; Xiaofeng Yang; Liemin Zhou (Reproductive Toxicology, 2025)

A promising strategy for selective recovery of Nb(V) using IRA-410 ion exchange resin: Adsorption performance and mechanism study - Congzhong Tian; Rui Ma; Wenjie Zou; Shifei Sun; Zhengyao Li; Zhijun Zhang; Fang Zhou (Journal of Environmental Chemical Engineering, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

Fe-induced d-orbital electron redistribution tailoring peroxymonosulfate activation pathway for efficient degradation of various antibiotics - Hongxin Shi; Chen Xu; Xinggang Liu; Fang Deng; Xibao Li; Jianping Zou; Xubiao Luo (Chemical Engineering Journal, 2025)

Oxygen-vacancy-induced interfacial BiS bond and internal electric field mediated charge transfer in S-scheme In2S3/BiOBr heterojunction for Cr (VI) photoreduction - Fang Deng; Li Chen; Yongcai Zhang; Xubiao Luo; Jianping Zou (Chemical Engineering Journal, 2025)

Antifungal cytochalasans from the co-culture of two endophytic fungi Aspergillus spelaeus and Xylaria sp - Xian-Hua He; Ye-Fang Hu; Hua-Chun Feng; Li-Qi Liang; Lan-Fang Zou; Qian Wu; Min Liang; Jun Li; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Geospatial environmental sources of inhaled microplastics: A case in Zhuhai, China - Chenghui Zhong; Meiqi Lan; Chunzhao Chen; Lieyang Fan; Hongjie Shen; Mengnan He; Jiajing Wang; Jingwen Fang; Wenfeng Lu; Xiaole Xu; Liqiu Qiu; Shaojuan Wang; et al. (Journal of Hazardous Materials, 2025)

Metabolic mechanism of a novel carboxylesterase YvaK in Priestia aryabhattai DPX-1 for carbamate insecticide indoxacarb detoxification - Ping Zou; Zijing Li; Shengyang Li; Yuehan Geng; Xin Ma; Xiangwei Wu; Rimao Hua; Liancheng Fang (Journal of Hazardous Materials, 2025)

Integration of multispectral imaging with colorimetric sensor arrays for rapid grading and volatile component prediction of Zhenjiang aromatic vinegar - Zhihua Li; Yi An; Xiaowei Huang; Wenbing Fang; Zhiming Guo; Jiyong Shi; Xiaobo Zou (Food Chemistry, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Pharmacokinetic study of Vibrio parahaemolyticus phage Фvp140 in Litopenaeus vannamei following oral administration - Di Fang; Laizhuang Jin; Qianhui Song; Xiong Zou; Lei Feng; Letian Li; Hui Zhang; Kun Hu; Mao Lin; Wenhong Fang (Aquaculture, 2025)

Green catalytic oxidation of m-diethylbenzene to m-ethylacetophenone with molecular oxygen over modified nano-sized TS-1 zeolite - Jinhong Li; Chang Cai; Yi’ning Wang; Zhimei Song; Dan Fang; Nan Zhao; Yue Zhang; Lidong Chen; Jianguo Zhang; Yongcun Zou (Journal of Environmental Chemical Engineering, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Glycerol-regulated interfacial adsorption behavior of whey protein isolate for stable high internal phase emulsion gels: Impact on lipid oxidation and curcumin bioaccessibility - Jinyu Miao; Hairan Ma; Xiuying Wu; Suqiong Fang; Liqiang Zou; Mengjie Zhu; Li Ma; Wei Liu; Ruiyun Chen (Food Hydrocolloids, 2025)

Stabilizing lithium metal batteries by anion modulated Quasi-Solid polymer electrolytes - Yifeng An; Renyi Li; Chi Fang; Wenchao Hu; Yang Yang; Aijun Li; Dubin Huang; Hsingkai Chu; Song Gao; Yonggang Wang; Jiaxin Zheng; Yatao Liu; et al. (Chemical Engineering Journal, 2025)

Characterization, Expression, and Functional Analysis of the Northern Snakehead (Channa argus) Hepcidin - Guowei Liao; Shulan Wang; Zimo Wang; Chaonan Zhang; Zicong Li; Huirong Yang; Aiguo Zhou; Shaolin Xie; Lanfen Fan; Meifang Wang; Jixing Zou; Fang Zeng (Probiotics and Antimicrobial Proteins, 2025)

Machine learning approaches for assessing medication transfer to human breast milk - Zhongyuan Zhao; Peng Zou; Yuan Fang; Tong Si; Yanyan Li; Bofang Yi; Tao Zhang (Journal of Pharmacokinetics and Pharmacodynamics, 2025)
The human milk/plasma (M/P) drug concentration ratio is crucial in pharmacology, especially for breastfeeding mothers undergoing treatment. It determines the extent to which drugs ingested by the mother pass into breast milk, potentially affecting the infant. This study conducted a comprehensive evaluation of multiple machine learning algorithms to assess their effectiveness in predicting the M/P ratio. The dataset consists of 162 drugs and 11 predictor variables. M/P ratios were categorized into two groups of (0, 1) and (≥ 1), and a refined three-category system: (0, < 0.5), (0.5, < 1), and (≥ 1). The ML techniques utilized include K-Nearest Neighbors (KNN), Random Forest, Support Vector Machine (SVM), and Neural Networks. We implied the five-fold cross-validation to ensure the model’s robustness and Principal Component Analysis (PCA) was applied for data visualization. Bayesian Information Criterion (BIC) was used in the KNN model selection to balance complexity and explanatory power. In our study, KNN achieved average accuracies of 79% for the two-category system and 60% for the three-category. Random Forest models show 77 and 64% average accuracy, respectively. SVM achieved similar results with 78 and 67%, while Neural Networks have the overall best result among the other models with average accuracies of 82 and 76% accuracy. The study highlights the potential of machine learning (ML) techniques in predicting M/P ratios, offering valuable insights for risk assessment during drug development. These predictive models can serve as a valuable tool for estimating drug transfer into breast milk, helping to bridge knowledge gaps in drug safety for lactating individuals. Further validation and refinement by incorporating larger datasets can enhance their reliability and applicability. Advancing these techniques can support safer medication use and informed clinical decision-making for lactating individuals.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Construction of Pd and PdCu alloy heterostructures for enhanced benzophenone hydrogenation performance - Bingcheng Li; Xinhui Zhang; Lili Zeng; Rubo Fang; Zihui Zou; Xinyi Zhang; Chunshan Lu; Qunfeng Zhang; Feng Feng; Qingtao Wang; Xiaonian Li (Fuel, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Effects of Probiotic-Fermented Chinese Herb on Immune Response and Growth Performance in Common Carp (Cyprinus carpio) - Wenzheng Zou; Xuanxuan Huang; Fang Han; Zhongqin Li (Fishes, 2025)
This study investigated the effects of fermented Chinese herb (FCH) on the growth indices, leukocyte activity, and biochemical indices of carp (Cyprinus carpio). Astragalus membranaceus (AM), Pericarpium Citri Reticulatae (PCR), and Glycyrrhizae Radix et Rhizoma (GRR) as feed additives enhance immune function, promote growth, and exert anti-inflammatory effects, respectively. Therefore, this study investigated the effects of co-fermented blends of these three herbs on growth performance and related parameters in common carp. By adding 2%, 5%, and 10% of the FCH to co-incubate with carp leukocytes, the results show that all three experimental treatments could enhance the respiratory burst activity and phagocytic activity of carp leukocytes. After 28 days of feeding with basal feed supplemented with 2%, 5%, and 10% (w/v) of the FCH, the weight gain rate and specific growth rate of carp were significantly higher than those of the control treatment without additives (ANOVA, p 0.05). However, the serum GPT activity in the 5% treatment was significantly lower than that of the control treatment (ANOVA, p

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

Effect of food addiction of lysine on feeding habit in fish - Hong-Liang Lu; Yun-Liang Miao; Jia-Ming Zou; Zi-Jun Hu; Ying-Cen Li; Xu-Fang Liang; Shan He (Aquaculture, 2025)

Alkaline catalytic liquefaction of pig manure fermentation residue in ethanol solvent for the production of high-quality biocrude oil - Jialong Tang; Jingchen Zou; Qianlan Li; Qingdan Wu; Xiaochen Zheng; Jun Fang; Zhihua Xiao (Waste Management, 2025)

How do environmental and operational factors impact particulate matter dynamics in building construction? - Insights from real-time sensing - Xingyue Fang; Ruidong Chang; Jian Zuo; Wei Emma Zhang; Yang Zou; Kaijian Li (Journal of Environmental Management, 2025)

Unveiling the distinctive characterization and adsorption behaviors of MnFe2O4 hydrochar/pyrochar composites for Cr(VI) removal - Wentao Zou; Fang Zhou; Zheng Zhang; Qichao Ruan; Jianlin Zhou; Zhixian Li; Guoliang Chen; Zhang Chen (Journal of Environmental Chemical Engineering, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Rhizosphere microecological mechanism of carbon sequestration and its emission mitigation in rice ratooning - Jinying Li; Bin Qin; Chaojie Lan; Hailong Xu; Jingnan Zou; Bianhong Zhang; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Agriculture, Ecosystems & Environment, 2025)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

Chemosensory protein 8 confers thiamethoxam resistance in Diaphorina citri - Qian Li; Wan-Wei Hu; Ao Fang; Zhuo-Bing Wang; Xiao-Fang Yuan; Yue Sun; Zheng-Hui Zou; Nuo Chen; Tian-Xing Jing; Ying-Xue Liu; Wei Chen; Hai-Zhong Yu; et al. (Pesticide Biochemistry and Physiology, 2025)

Identification and functional characterization of an antennal glutathione S-transferase in Protegira songi (Lepidoptera Noctuidae) - Jie Zou; Mengqing Zhang; Xi Wen; Yue Zhang; Zhi Li; Fang Yuan; Xiaochao Tang; Sijie Xiao; Tong Shen; Xiangrong Tian; Xinglong Huang; Li Yang (Journal of Asia-Pacific Entomology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mechanistic impact of Gracilaria bailinae extracts on photosynthesis and metabolism in Phaeodactylum tricornutum - Li-Gong Zou; Fu-Fang Wen; Xiao Zhang; Gang Li; Qing Wang; Hong-Ye Li; Yu-Feng Yang (Marine Environmental Research, 2025)

CD33 Ameliorates Surgery-Induced Spatial Learning and Memory Impairments Through TREM2 - Jie Zou; Yaxuan Wang; Xinyue Zhang; Xue Pan; Te Fang; Dasheng Cai; Lili Guo; Yu Li; Yi He; Xuezhao Cao (Molecular Neurobiology, 2025)

The role of phenology in crop yield prediction: Comparison of ground-based phenology and remotely sensed phenology - Jie Pei; Shaofeng Tan; Yaopeng Zou; Chunhua Liao; Yinan He; Jian Wang; Huabing Huang; Tianxing Wang; Haifeng Tian; Huajun Fang; Li Wang; Jianxi Huang (Agricultural and Forest Meteorology, 2025)

Origin for dark catalytic performance of sulfide-based photocatalysis: Vital role of sulfur vacancy in charge storage and release - Chunsong Zhang; Zixuan Zheng; Zhenzhou Wang; Fang Deng; Xibao Li; Jianping Zou (Chemical Engineering Journal, 2025)

Low mechanical-hysteresis conductive hydrogel conferred by chitosan bridging and MXene nanoconfined mechanism - Jian Zou; Xin Jing; Shitao Li; Yi Chen; Yuejun Liu; Pei-Yong Feng; Xiang-Fang Peng (Carbohydrate Polymers, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Environmental risk control of florfenicol in water: From technology selection to mechanism discussion - Weilai Wang; Jinghan Li; Menghao Fang; Yu Chang; Tian Wang; Xinyang Wang; Haijin Liu; Wei Zou; Zhiguo Cao (Journal of Environmental Chemical Engineering, 2024)

Photodegradation of ciprofloxacin and its interaction with Cu(II) in different water matrices: Insight into degradation pathways - Fang Zhong; Wenyu Huang; Xiaoqing Feng; Jia Zhang; Hongrui Zhang; Yiwu Dong; Jingrao Li; Liang Zou; Feishu Cao; Gilles Mailhot (Environmental Pollution, 2024)

Driving factors of the distribution of microplastics in the surface soil of the typical uninhabited and habited areas in the Qinghai–Tibet plateau, China - Linyue Dai; Ruiqi Dou; Chunlong Jiang; Qinghai Xu; Yuecong Li; Fang Tian; Jifeng Li; Huiru Li; Zixiao Guo; Xueyong Zou; Chunping Chang; Zhongling Guo (Environmental Pollution, 2024)

Similarities and differences in bacterial communities between the Pearl River (Guangzhou section) and its estuary - Longxin Wang; Wencheng Zhao; Yun Jiang; Li Liu; Jianwei Chen; Fang Zhao; Xiaoyong Zhang; Keshu Zou (Molecular Biology Reports, 2024)

Litter, root, and mycorrhiza manipulations and seasonal effects on soil physicochemical properties and microbial communities in a subtropical coniferous and broad-leaved mixed forest - Liqin Zhu; Rongzhen Huang; Hongzhi Guan; Jinping Wang; Zhijun Huang; Huanying Fang; Xianhua Zou; Jingkai Li; Pingyu Liu (Applied Soil Ecology, 2024)

Spatiotemporal distribution characteristics of fracturing fluid in multiscale pore structure of deep marine shale gas reservoirs - Peisong Li; Mingjun Chen; Yili Kang; Hua Liu; Sidong Fang; Lijun You; Zhehan Lai; Yeyu Zou (Fuel, 2024)

Dual cation Kgu/PAM Gel polymer electrolyte with high ionic conductivity and mechanical strength for flexible All-Solid-State supercapacitors - Kaijun Xie; Xin Liu; Baichuan Mo; Tingting Li; Kai Xia; Long Fang; Yihui Zou; Dongjiang Yang; Xiaodong Zhang (Chemical Engineering Journal, 2024)

A novel antidepressant homogeneous polysaccharide YLP-1 from Millettia pulchra ameliorates tryptophan metabolism and SCFAs through modulating gut microbiota - Meng Yu; Cong-Cong Cai; Yun-Feng Huang; Yin-Di Zhu; Xin-Yao Luo; Xin-Yu Kong; Wen-Ting Zhang; Hui-Jun Li; Jing-Xian Fang; Zhong-Mei Zou (Carbohydrate Polymers, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Simulation and experimental study of gas-phase diffusion coefficient of selenium dioxide - Xiaolong Wu; Renjie Zou; Guangqian Luo; Li Wang; Can Fang; Sheng Chen; Xian Li; Hong Yao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Contribution to energy conservation and quality improvement of frozen pork via contact/contactless immersion freezing in NaCl solution - Yu Zhou; Xia Yu; Ran Xiao; Li-fang Zou; Qing-fei Du; Fei Ma; Cong-gui Chen (Meat Science, 2024)

An accurate and efficient forecast framework for fine PM2.5 maps using spatiotemporal recurrent neural networks - Ning Liu; Bin Zou; Yi Li; Zengliang Zang; Shan Xu; Sha Li; Shenxin Li; Lu Zhi; Jun Chen; Fang Zhao (Journal of Cleaner Production, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Enhancement of selenium removal in coal-fired flue gas across wet flue gas desulfurization spray tower by internal components-part 1: Demister and wall ring - Renjie Zou; Zehua Li; Guangqian Luo; Haoyu Zhang; Can Fang; Li Wang; Min Lyu; Yongda Huang; Sheng Chen; Xian Li; Hong Yao (Journal of Cleaner Production, 2024)

The crustal structure of southeast Tibet from joint inversion of surface wave dispersion and gravity anomaly data - Haopeng Chen; Ruirui Fan; Nanqiao Du; Feng Bao; Zeming Zhang; Xuelei Li; Fang Zou; Chuang Xu (Journal of Asian Earth Sciences, 2024)

Rapidly reversible superwettability on textured metallic surfaces - Xianrui Zou; Yongguang Zhang; Wei Fang; Hui Jiang; Zhilu Yang; Qunyang Li; Shuilin Wu; Hongshui Wang; Donghui Wang; Huan Zhou; Tai Yang; Dan Xia; et al. (Chemical Engineering Journal, 2024)

An injectable COL6-crosslinked HA-DTPH hydrogel promotes spinal tract-like structure organization during spinal cord regeneration - Jia-Hui Sun; Zhou Fang; Zhiling Li; Ting-Ting Zheng; Sheng Liu; Jixiang Zhu; Wensheng Lin; Li-Kang Zhang; Aihua Yin; Aiguo Xuan; Jian-Long Zou (Chemical Engineering Journal, 2024)

Microwave-assisted preparation of yellow fluorescent graphitic carbon nitride quantum dots for trace tetracycline-specific detection - Yanzhi He; Xiaopei Li; Guixiang Yao; Shuju Fang; Hang Yu; Tianru Zou; Wei Tan; Hongbin Wang (Chemosphere, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Contrasting hydrocarbon reservoirs in the North China Craton in relation to inhomogeneous craton destruction - Caineng Zou; Yong Li; Xiao-Fang He; M. Santosh; Kun Yu; Ross N. Mitchell (Earth-Science Reviews, 2024)

Isoprene emission dynamics in Chaetoceros curvisetus: Insights from transcriptome analysis under light/dark cycles - Danna Zhao; Runqi Li; Guizhen Fang; Yee Jun Tham; Shichun Zou; Zhenhao Ling; Ying Yang (Algal Research, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Regulation of photoassimilate transportation and nitrogen uptake to decrease greenhouse gas emissions in ratooning rice with higher economic return by optimized nitrogen supplies - Jingnan Zou; Hailong Xu; Chaojie Lan; Bin Qin; Jinying Li; Witness Joseph Nyimbo; Hongmei Lin; Ziqin Pang; Nyumah Fallah; Chunlin Guo; Changxun Fang; Zhixing Zhang; et al. (Field Crops Research, 2024)

Two new chromone derivatives from the rhizosphere soil fungus Ilyonectria robusta - Min Kuang; Wei-Wei Peng; Yuan-Tao Huang; Mei-Fang Li; Si-Yu Qin; Yu-Ting Zheng; Li Xu; Qi Huang; Zhen-Xing Zou (Natural Product Research, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

Boosting the photochromic property of KSr2Nb5O15-based ceramics through an indirect vacancy-regulation strategy - Shuyao Cao; Yufan Zhang; Qirui Zou; Qinfu Zhao; Fang Kang; Qiwei Zhang; Leilei Li; Qian Chen; Ziyi Xu; Weiguo Wang; Feng Gao (Chemical Engineering Journal, 2024)

Corrigendum to “A OH self -suppling and dual regulation hybrid nanozyme combined with photothermal therapy to eliminate biofilms and eradicate infections” [Chem. Eng. J. 481 (2024) 148613] - Jiazhuo Song; Fang Li; Xinying Zou; Hamed Alshawwa; Minghan Chi; Guinong Qiao; Ruijing Shang-Guan; Wenjun Tang; Lihua Hong; Zhimin Zhang (Chemical Engineering Journal, 2024)

Severe Global Environmental Issues Caused by Canada’s Record-Breaking Wildfires in 2023 - Zhe Wang; Zifa Wang; Zhiyin Zou; Xueshun Chen; Huangjian Wu; Wending Wang; Hang Su; Fang Li; Wenru Xu; Zhihua Liu; Jiaojun Zhu (Advances in Atmospheric Sciences, 2024)

STS ⅡA inhibited angiogenesis of lung adenocarcinoma by activating FOXO3 to inhibit CXCL1/STAT3/VEGF pathway - Bu Wang; Fang Zou; Gu Xin; Bao-Li Xiang; Jian-Qing Zhao; Sheng-Fang Yuan; Xiu-Long Zhang; Zhi-Hua Zhang (Toxicon, 2024)

The structural and functional properties of a novel enzyme-modified starch as an alternative to hydroxypropyl starch ether - Ruobing Li; Haiteng Tao; Congping Tan; Fang Yuan; Li Guo; Bo Cui; Yu Zhu; Feixue Zou; Pengfei Liu; Lu Lu (Food Hydrocolloids, 2024)

Functional characterization of RIP2 in large yellow croaker (Larimichthys crocea), a protein involved in the host antiviral responses via NF-κΒ, IRF3/7 related signaling - Jing Jiang; Ying Li; Kai Qing Li; Ying Jia Shen; Fang Li; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

A ·OH self-suppling and dual regulation hybrid nanozyme combined with photothermal therapy to eliminate biofilms and eradicate infections - Jiazhuo Song; Fang Li; Xinying Zou; Hamed Alshawwa; Minghan Chi; Guinong Qiao; Ruijing Shang-Guan; Wenjun Tang; Lihua Hong; Zhimin Zhang (Chemical Engineering Journal, 2024)

Boosting the charge transport and stability of metal halide perovskite with boron nitride nanosheets for X-ray detection and imaging - Fang Yao; Zhenglin Jia; Junqi Dong; Ruiming Li; Yujie Yang; Haitao Tang; Wusheng Zou; Jiangbin Zhao; Yong Liu; Zhu Wang; Gaokui He; Qianqian Lin (Chemical Engineering Journal, 2024)

Effects of polyols with different hydroxyl numbers on the structure and properties of starch straws - Chenyu Ma; Haiteng Tao; Congping Tan; Shijun Gao; Zehua Wu; Li Guo; Bo Cui; Fang Yuan; Feixue Zou; Pengfei Liu; Lu Lu (Carbohydrate Polymers, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Insights into the in vitro digestibility of pork myofibrillar protein with different ionic polysaccharides from the perspective of gel characteristics - Xia Yu; Xi-xi Wang; Li-fang Zou; Ke-zhou Cai; Jing-zhi Pan; Cong-gui Chen (Food Chemistry, 2023)

Thin continuous membrane coating with high surface energy for comprehensive antifouling seawater distillation - Yuandong Jia; Kecheng Guan; Zhaohuan Mai; Shang Fang; Zhan Li; Pengfei Zhang; Dong Zou; Xiaobin Jiang; Gaohong He; Hideto Matsuyama (Water Research, 2023)

Enhanced conversion kinetics by constructing boron and nitrogen co-doped porous carbon with sulfurophilic and sodiophilic sites in room-temperature sodium-sulfur batteries - Qiuyang Ma; Haoda Zou; Hengli He; Yue Li; Zhen Fang (Chemical Engineering Journal, 2023)

Meso- and microplastic contamination in mulching cultivated soil at a national scale, China - Yinghao Xue; Jing Li; Tuo Jin; Dongsheng Liu; Guoyuan Zou; Fang Li; Kang Wang; Li Xu (Journal of Cleaner Production, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Production of single-crystal Cu plates by electrodeposition on high-index Cu foils - Xingguang Li; Zhihong Zhang; Zhibin Zhang; Jinzong Kou; Muhong Wu; Mengze Zhao; Ruixi Qiao; Zhiqiang Ding; Zhiqiang Zhang; Fang Liu; Xiaonan Yang; Dingxin Zou; et al. (Science Bulletin, 2023)

High prevalence and genomic characteristics of carbapenem-resistant Enterobacteriaceae and colistin-resistant Enterobacteriaceae from large-scale rivers in China - Cai-Hong Guo; Yu-Qing Liu; Yan Li; Xiao-Xiao Duan; Ting-Yu Yang; Fang-Yu Li; Ming Zou; Bao-Tao Liu (Environmental Pollution, 2023)

Cellulose sulfate lithium as a conductive binder for LiFePO4 cathode with long cycle life - Xu Su; Han Fang; Hao Yang; Fangfang Zou; Gang Li; Lian Wang; Hongxin Liao; Wei Guan; Xuebu Hu (Carbohydrate Polymers, 2023)

CNTN1 in the Nucleus Accumbens is Involved in Methamphetamine-Induced Conditioned Place Preference in Mice - Linxuan Zhang; Zehao Zeng; Xiaoyu Lu; Mengqing Li; Jiayu Yao; Guangjing Zou; Zhaorong Chen; Qian Li; Changqi Li; Fang Li (Neurotoxicity Research, 2023)

Comparative study of ionospheric sporadic E occurrence rates using SNRnstd and S4 derived from GPS radio occultation - Long Tang; Jiaxing Li; Fenkai Zhang; Fang Zou (GPS Solutions, 2023)

Ag quantum dots decorated ultrathin g-C3N4 nanosheets for boosting degradation of pharmaceutical contaminants: Insight from interfacial electric field induced by local surface plasma resonance - Zhenzhou Wang; Danqi Wang; Fang Deng; Xinggang Liu; Xibao Li; Xubiao Luo; Yanzhi Peng; Jian Zhang; Jianping Zou; Lin Ding; Longshuai Zhang (Chemical Engineering Journal, 2023)

Risk assessment and optimization of supporting structure for a new recyclable pipe jacking shaft during excavation process - Chao Zhang; Yunhui Zhang; Yangyang Xia; Hongyuan Fang; Peng Zhao; Cuixia Wang; Bin Li; Yanhui Pan; Zhihui Zou; Timon Rabczuk; Xiaoying Zhuang (Process Safety and Environmental Protection, 2023)

Complementary use of generalized logistic mixture model and distributed activation energy model in exploring kinetic mechanisms of wheat straw and torrefied rice husk pyrolysis - Jianfeng Zou; Hangli Hu; Yingkai Li; Hessam Jahangiri; Fang He; Xingguang Zhang; Md Maksudur Rahman; Junmeng Cai (Journal of Cleaner Production, 2023)

Rapid room-temperature polymerization strategy to prepare organic/inorganic hybrid conductive organohydrogel for terahertz wave responsiveness - Haihan Zou; Peng Yi; Wenbin Xu; He Cai; Junzhe He; Xin Sun; Xufeng Li; Chunyan Chen; Gao Deng; Yingbo Yuan; Zhenyang Li; Ming Fang; et al. (Chemical Engineering Journal, 2023)

Polysaccharide extracted from pomelo fruitlets attenuate hepatic lipid accumulation in hybrid groupers (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) - Cuiyun Zou; Yuke Fang; Nuoyi Lin; Gengsheng Xiao; Li Lin; Huifan Liu (Frontiers in Marine Science, 2023)
Introduction Pomelo is one of the most consumed fruits due to its distinct flavor and sour taste, while large quantities of pomelo fruitlets discard during cultivation and most of them are disposed of as wastes. Such an issue has led to some research on how to make a high value-added reutilization of these fruitlets. Therefore, it was aimed to determine the structural characteristics of the polysaccharide of pomelo fruitlets and evaluate its attenuating effect on the hepatic lipid accumulation in hybrid groupers ( Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀ ). Methods and results In this research, YZ-0.5A is a 15,332 Da NaCl-soluble polysaccharide extracted from pomelo fruitlet which was characterized to mainly contain galactose and galacturonic acid and its putative structure was proven to be →2,4)- α-L-Rhap-(1→4)-α-D-GalAp-(1→4)-α-D-GalAp-(1→ with 3 branches. In vivo study, five isolipidic diets (containing 15% lipid) were fed to the groupers with an initial weight of 13.46 ± 0.08 g for 8 weeks, of which the dietary level of YZ-0.5A was 0 mg/kg (control), 150 mg/kg, 300 mg/kg, 600 mg/kg and 1200 mg/kg respectively. We found that the treatment of YZ-0.5A, especially 600 mg/kg, exerted an improved effect on the excessive lipid accumulation in grouper fed with a high-fat diet. In vitro , three graded concentrations of YZ-0.5A (75, 150 or 300 μg/ml) were added to the grouper primary hepatocytes respectively after incubation with 20% lipid emulsion (2 ml/L). The signs of recovery on morphological features observed under examined by histological evaluation supported the lipid lowering effect of YZ0.5-A. Further investigation showed that YZ0.5-A mitigated lipid emulsion-induced irregular lipid deposition by regulating various lipometabolism-related indicators, thereby alleviating oxidative stress and apoptosis. Discussion Overall results exhibited the therapeutic potential of YZ0.5-A and elucidated its underlying mechanism in the fish with excessive lipid deposition, which first suggested the feasibility of reprocessing discarded pomelo fruitlet as medicine in aquaculture.

Effect of β-glucosidase on the aroma of liquid-fermented black tea juice as an ingredient for tea-based beverages - Shuang Liang; Fang Wang; Daniel Granato; Xiaoyu Zhong; An-Feng Xiao; Qun Ye; Lijun Li; Chun Zou; Jun-Feng Yin; Yong-Quan Xu (Food Chemistry, 2023)

Numerical simulation and optimization of coupled demister with directing and perforated plate in MSF plants - Can Fang; Renjie Zou; Guangqian Luo; Chengshuai Li; Min Lv; Li Wang; Haoyu Zhang; Hong Yao (Desalination, 2023)

A spatial model for coastal flood susceptibility assessment using the 2D-SPR method with complex network theory: A case study of a reclamation island in Zhoushan, China - Xin Fang; Yifei Zhang; Yunyun Xiang; Jiaqi Zou; Xiaoyan Li; Chunling Hao; Jingchen Wang (Environmental Impact Assessment Review, 2023)

Novel ZnFe2O4/Bi2S3 high-low junctions for boosting tetracycline degradation and Cr(VI) reduction - Biguo Yan; Junlong Peng; Fang Deng; Lingling Liu; Xibao Li; Penghui Shao; Jianping Zou; Shuqu Zhang; Jie Wang; Xubiao Luo (Chemical Engineering Journal, 2023)

Self-healing properties of retrograded starch films with enzyme-treated waxy maize starch as healing agent - Li Guo; Na Yang; Wei Gao; Haiteng Tao; Bo Cui; Pengfei Liu; Feixue Zou; Lu Lu; Yishan Fang; Zhengzong Wu (Carbohydrate Polymers, 2023)

Detection and assessment of dust mite allergens in an indoor environment in Anhui, China - Qiqi Xue; Minghui Zou; Junjie Guo; Qiao Teng; Qiqi Zhang; Lingwei Sheng; Sijia Xu; Can Fang; Ning Yao; Yuanyuan Li; Jinhong Zhao (Environmental Science and Pollution Research, 2023)
Dust in the home environment is thought to be a potential trigger for increasing allergic diseases, such as allergic rash, rhinitis, asthma, and other conditions, associated with dust mites. To verify the status of dust mite prevalence in indoor surroundings, we collected 189 dust samples from the air conditioner filters ( n = 75) and floors ( n = 114) of households, schools, and hotels in the Anhui area, China. All samples were measured for dust mite breeding rate and breeding density under light microscopy and analyzed for dust mite species Dermatophagoides farinae 1 (Der f 1) and Dermatophagoides pteronyssinus 1 (Der p 1) allergen using enzyme-linked immunosorbent assay (ELISA). The dust mite breeding rates were 34.67% (26/75) and 20.18% (23/114), respectively, in the dust samples from the floor and air conditioning filters. The breeding density was the highest in households (10/g), followed by schools (9/g) and hotels (4/g). ELISA indicated that the allergen threshold (2.0 µg/g dust) of Der f 1 was exceeded in only two samples and Der p 1 in one sample. Additionally, a questionnaire was used to investigate the health knowledge on allergic diseases involved in indoor facilities, finding that most allergy sufferers were aware that indoor dust might be responsible for their conditions. The findings suggest that regular maintenance of indoor hygiene and cleaning of air-conditioning filters should reduce the risks of exposure to indoor allergens.

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

FUS Mutation Causes Disordered Lipid Metabolism in Skeletal Muscle Associated with ALS - Binbin Zhou; Yilei Zheng; Xiaobing Li; Huifang Dong; Jiaxi Yu; Yang Zou; Min Zhu; Yanyan Yu; Xin Fang; Meihong Zhou; Wei Zhang; Yun Yuan; et al. (Molecular Neurobiology, 2022)

Distribution of trace metals in a soil–tea leaves–tea infusion system: characteristics, translocation and health risk assessment - Bin Yang; Shuang Ren; Kexin Zhang; Song Li; Zhongwei Zou; Xue Zhao; Jinqiu Li; Yuanchun Ma; Xujun Zhu; Wanping Fang (Environmental Geochemistry and Health, 2022)

A novel SCARECROW-LIKE3 transcription factor LjGRAS36 in Lotus japonicus regulates the development of arbuscular mycorrhizal symbiosis - Yunjian Xu; Fang Liu; Fulang Wu; Manli Zhao; Ruifan Zou; Jianping Wu; Xiaoyu Li (Physiology and Molecular Biology of Plants, 2022)

TREM2 Ameliorates Lipopolysaccharide-Induced Oxidative Stress Response and Neuroinflammation by Promoting Sirtuin3 in BV2 Cells - Hongqing Li; Fang Liu; Wenwen Jiang; Kexin Wang; Xuezhao Cao; Jie Zou; Yongjian Zhou; Zhe Li; Sidan Liu; Xiaotong Cui; Xinyue Zhang (Neurotoxicity Research, 2022)

The genomic history of southwestern Chinese populations demonstrated massive population migration and admixture among proto-Hmong–Mien speakers and incoming migrants - Yicheng Wang; Xing Zou; Mengge Wang; Didi Yuan; Li Yang; Yujie Zeng; Fang Cheng; Renkuan Tang; Guanglin He (Molecular Genetics and Genomics, 2022)

Long-term high-intensity interval training increases serum neurotrophic factors in elderly overweight and obese Chinese adults - Xi Li; Tianyu Han; Xu Zou; Han Zhang; Wenpin Feng; Han Wang; Yulin Shen; Li Zhang; Guoliang Fang (European Journal of Applied Physiology, 2021)

Carbon and nitrogen budget in fish-polychaete integrated aquaculture system - Fawen Hu; Ming Sun; Jinghui Fang; Guodong Wang; Li Li; Fengxiang Gao; Yuxia Jian; Xue Wang; Guangbin Liu; Yan Zou; Wen Guo (Journal of Oceanology and Limnology, 2021)

Correction to: P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2',3'-dideoxycytidine - Zhihua Yi; Lihui Xie; Congfa Zhou; Huilong Yuan; Shuai Ouyang; Zhi Fang; Shanhong Zhao; Tianyu Jia; Lifang Zou; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2021)

Propylenella binzhouense gen. nov., sp. nov. isolated from activated sludge, and proposal of Propylenellaceae fam. nov. - Yu-Ling Liu; Dong Meng; Fang Wang; Xiao-Fan Gong; Peng-Fei Gu; Xiang-Yu Fan; Zong-Jun Du; Ji-Dong Zou; Qiang Li (Antonie van Leeuwenhoek, 2021)

Long-term Outcomes and Risk Factors Related to Hydrocephalus After Intracerebral Hemorrhage - Rong Hu; Chao Zhang; Jiesheng Xia; Hongfei Ge; Jun Zhong; Xuanyu Fang; Yongjie Zou; Chuan Lan; Lan Li; Hua Feng (Translational Stroke Research, 2021)

Etv5 safeguards trophoblast stem cells differentiation from mouse EPSCs by regulating fibroblast growth factor receptor 2 - Kui Zhu; Yuan Liu; Chen Fan; Mengyao Zhang; Hongxia Cao; Xin He; Na Li; Dianfeng Chu; Fang Li; Min Zou; Jinlian Hua; Huayan Wang; et al. (Molecular Biology Reports, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Olfaction is a Marker of Severity but Not Diagnosis in Anorexia Nervosa: a Systematic Review and Meta-Analysis - Yiling Mai; Xin Zhang; Zetian Li; Xiaohua Wu; Baoer Zeng; Yuan Fang; Laiquan Zou; Jiubo Zhao; Thomas Hummel (Neuropsychology Review, 2020)

Independent Component Analysis and Graph Theoretical Analysis in Patients with Narcolepsy - Fulong Xiao; Chao Lu; Dianjiang Zhao; Qihong Zou; Liyue Xu; Jing Li; Jun Zhang; Fang Han (Neuroscience Bulletin, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Pharmacokinetics of enrofloxacin and its metabolite ciprofloxacin in Pacific white shrimp Litopenaeus vannamei after multiple-dose oral administration - Rongrong Ma; Liang Huang; Wenjuan Wei; Yuan Wang; Xiong Zou; Junfang Zhou; Xincang Li; Wenhong Fang (Fisheries Science, 2018)

Association of rs4552569 and rs17095830 single-nucleotide polymorphisms with susceptibility to ankylosing spondylitis in east Asian population: a meta-analysis - Shutao Gao; Huan Wang; Chuankun Zhou; Ming Guan; Xiao Li; Jun Dai; Yinshuang Zou; Huang Fang (Journal of Genetics, 2018)

P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2′,3′-dideoxycytidine - Zhihua Yi; Lihui Xie; Congfa Zhou; Huilong Yuan; Shuai Ouyang; Zhi Fang; Shanhong Zhao; Tianyu Jia; Lifang Zou; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2018)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Synthesis of some new thiazolo[3,2-a]pyrimidine derivatives and screening of their in vitro antibacterial and antitubercular activities - Dong Cai; Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Shi-Ti Zhang; Liang-Jing Zou; Li-Hong Meng; Fang Li; Bing-Jie Fu (Medicinal Chemistry Research, 2016)

Thermal evolution and applications of aromatic hydrocarbons in highly mature coal-bearing source rocks of the Upper Triassic Xujiahe Formation in the northern Sichuan Basin - Ying Li; YangMing Zhu; Fang Hao; HuaYao Zou; TongLou Guo (Science China Earth Sciences, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Pig transgenesis by piggyBac transposition in combination with somatic cell nuclear transfer - Zhenfang Wu; Zhiqian Xu; Xian Zou; Fang Zeng; Junsong Shi; Dewu Liu; Johann Urschitz; Stefan Moisyadi; Zicong Li (Transgenic Research, 2013)

Altered Methylation of the DNA Repair Gene MGMT Is Associated with Neural Tube Defects - Susanna Tran; Li Wang; Jing Le; Jing Guan; Lihua Wu; Jizhen Zou; Zhen Wang; Jianhua Wang; Fang Wang; Xiaoli Chen; Lingling Cai; Xiaolin Lu; et al. (Journal of Molecular Neuroscience, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

Glutamate carboxypeptidase II gene polymorphisms and neural tube defects in a high-risk Chinese population - Hua Xie; Jin Guo; Jianhua Wang; Fang Wang; Huizhi Zhao; Chi Liu; Li Wang; Xiaolin Lu; Lihua Wu; Yihua Bao; Jizhen Zou; Ting Zhang; et al. (Metabolic Brain Disease, 2012)

Meta-analysis of TYK2 gene polymorphisms association with susceptibility to autoimmune and inflammatory diseases - Jin-Hui Tao; Yan-Feng Zou; Xiao-Liang Feng; Jing Li; Fang Wang; Fan-Ming Pan; Dong-Qing Ye (Molecular Biology Reports, 2011)

Fungistatic Intensity of Agricultural Soil Against Fungal Agents and Phylogenetic Analysis on the Actinobacteria Involved - Li Zhi Fang; Xu Chuan Kun; Zou Chang Song; Xi Jia Qin; He Yue Qiu; Duan Chang Qun; Mo Ming He (Current Microbiology, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Genetic analysis revealed LX4 genotype strains of avian infectious bronchitis virus became predominant in recent years in Sichuan area, China - Nian-Li Zou; Fang-Fang Zhao; Yuan-Ping Wang; Ping Liu; San-Jie Cao; Xin-Tian Wen; Yong Huang (Virus Genes, 2010)

The global image of the Moon obtained by the Chang’E-1: Data processing and lunar cartography - ChunLai Li; JianJun Liu; Xin Ren; LingLi Mou; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; et al. (Science China Earth Sciences, 2010)

Expression Profiles of Class A Rice Heat Shock Transcription Factor Genes Under Abiotic Stresses - Ai-Ling Liu; Jie Zou; Xian-Wen Zhang; Xiao-Yun Zhou; Wen-Fang Wang; Xing-Yao Xiong; Li-Yun Chen; Xin-Bo Chen (Journal of Plant Biology, 2010)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)